Earnings Management And Privatisations: Evidence From Pakistan Evidence From Pakistan (The Pakistan Development Review, 2015)
This study examines the incidence of earnings management around the time of the privatisation of State Owned Enterprises in Pakistan during 1991-2005. Using the modified Jones model and a sample of large privatisations (minimum US$1 million), it shows that the sampled firms experienced increase in earnings, decrease in cash flows, and increase in current discretionary accruals in the year prior to and/or in the year of privatisation. The SOEs used both short term and long term accruals to inflate reported earnings. These accruals were reversed in the post-privatisation period. These findings suggest that managers of the firms slated for privatisation were engaged in earnings management to inflate their firms‘ financial worth to maximise the privatisation proceeds. Hence, we cannot reject the incidence of earnings management during privatisations in Pakistan. The results imply that the investors should carefully evaluate the to-be-privatised firms and keep in view the possibility of earnings management by the SOEs. JEL Classification: G14, G34, G38, L33, M41 Keywords: Earnings Management, Privatisations, SOEs, Pakistan, Accruals